Inovasi Pelayanan Informasi melalui Aplikasi Sentuh Tanahku pada Kantor Pertanahan Kota Administrasi Jakarta Utara - Yola Amanda Putri; Roni Ekha Putera; Wewen Kusumi Rahayu (Pencerah Publishing, 2022)
In order to encourage transparency and improve the quality of public services, information service innovation through the Sentuh Tanahku Application is present as a public service which made by the Ministry of Agrarian Spatial Planning/National Land Agency and applied to all communities and the Land Office in Indonesia. Through the Sentuh Tanahku application, you can provide land services simply and control land assets efectively by community. However, the application of the Sentuh Tanahku Application in North Jakarta City is still slightly inclined even though the North Jakarta Administrative City Land Office is one of the best land office in Indonesia. The purpose of this research is to analyze the Sentuh Tanahku Application in the North Jakarta Administration City Land Office with qualitative research methods and data collection techniques with interview and documentation methods. This research is adapted to the Theory of Innovation Attributes from Rogers. The results showed that the Sentuh Tanahku Application Innovation at the North Jakarta City Land Administration Office had fulfilled all the components in the Innovation Attribute Theory, but in its use there were still some problems, many obstacles comes in operating the Loketku Feature and the Field Plot Feature by the North Jakarta City Community and the lack of socialization carried out. by the North Jakarta Administrative City Land Office, so that there is still need maintanances in the Sentuh Tanahku application feature so that the Touch Tanahku application can help fulfill the land service needs of the people of North Jakarta City.